Divisi Nafkah, Qiwamah, and Gender in Islamic Family Law: Between Patriarchal Construction and Egalitarian Reconstruction - Nur Aula Yazid (VRISPRAAK : International Journal of Law, 2026)
The concepts of nafkah (spousal financial maintenance) and qiwamah (male guardianship) stand as the two most contested pillars of Islamic family law, occupying the intersection between centuries-old jurisprudential tradition and contemporary demands for gender justice. This article examines the classical construction of nafkah and qiwamah in Islamic jurisprudence and their codification in Indonesian positive law the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) and the Marriage Law No. 1 of 1974 before analyzing the growing body of gender-critical scholarship that challenges their patriarchal underpinnings. Drawing on a qualitative-normative methodology with a comparative and gender-analytical approach, this study synthesizes recent academic literature (2018–2025) alongside primary sources including Qur’anic texts, classical fiqh manuals, and contemporary fatwas. The findings reveal that traditional nafkah which assigns exclusive financial responsibility to the husband and qiwamah which legitimizes singular male leadership are facing fundamental challenges from gender-sensitive interpretive frameworks. Reconstructive paradigms grounded in mub?dalah (reciprocity), maq??id al-shar?‘ah (higher objectives of Islamic law), and principles of substantive equality offer a compelling alternative in which nafkah is understood as a shared, capacity-based responsibility and qiwamah is reconceptualized as functional, consultative co-leadership. This article argues that responsive ijtih?d and fatwa issuance attentive to modern social realities, human rights norms, and the spirit of Islamic justice are essential for reforming Islamic family law in ways that are both authentically Islamic and genuinely equitable.